IMPLEMENTASI SISTEM SUPPORT SERVICE BERBASIS ANDROID DENGAN NAIVE BAYES, PRIORITY QUEUE, DAN LOAD BALANCING SERTA EVALUASI KEPUASAN PELANGGAN - Wahyu Eko Suroso (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Currently, the customer service process in the Service and Support Department of PT X is still carried out semi-manually through email, telephone, and instant messaging. This condition causes report recording to be less structured, increases the risk of data loss, slows complaint handling, and reduces transparency in ticket resolution status. As a result, operational efficiency decreases and customer satisfaction with the service becomes less optimal for the company. This research develops an Android-based support service ticketing application integrated with cloud-based data storage and real-time notifications. The system applies the Naive Bayes method to classify ticket priority levels based on complaint descriptions, Priority Queue to manage service queues according to urgency, and Load Balancing to distribute technician tasks evenly based on workload. The development method used is Agile Software Development with a Scrum approach through planning, development, testing, and continuous evaluation stages in each sprint. The results show that the system can improve service efficiency by 35%, accelerate technician response by 40%, reduce the risk of data loss by up to 90%, and achieve a user satisfaction level of 88% based on UserAcceptance Test (UAT) results. This system also improves service transparency, real-time ticket monitoring, and service management decision making.